(untitled) (Altre Modernità, 2017)
In the work of the Argentinian writer Alejandra Pizarnik (1936-1972), the disintegration of the subject is tied to the use of (pro)nouns and their several multiplications. The linguistic and textual strategies employed to convey a symbolic representation of sexuality witness a voice whose sexual, national, ethnic and cultural identity is transitive and transgressive - thus questioning the traditional identity pillars imposed by the Western (Euro-North-American) heteronormativity. In the last years of the writer’s life, the struggle with language was intertwined with a psycophysical condition that caused regular hospitalizations but laid the basis for a borderline experience which fostered literary creations. In them, her monitored, punished and transformed corporeality still found a way to transgress the rules of the ‘disciplinary’ society.